Kajian Teoritis: Meningkatkan Efektivitas Proyek Konstruksi Menggunakan Lean, Green, dan Six Sigma - Ly, Aditya (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Sustainable development and growing public awareness of waste and project optimization have become priorities in the construction industry. Lean is a management approach aimed at reducing waste of time and resources. Green emphasizes managing environmental waste through life-cycle evaluation of products and processes. Meanwhile, Six Sigma fokuses on controlling variation and improving process quality to reduce defects. This study aims to theoretically analyze the effectiveness of integrating Lean, Green, and Six Sigma to improve construction project performance. The literature review approach shows that combining these three methods can compensate for individual limitations and create a more resilient system to address waste, energy efficiency, and product quality. In construction, this integration not only reduces costs and time but also contributes significantly to environmental sustainability. Therefore, Lean, Green, and Six Sigma form a strategic and effective combination to enhance efficiency, quality, and sustainability in modern construction projects